2006
DOI: 10.1002/nme.1959
|View full text |Cite
|
Sign up to set email alerts
|

Numerical exploration of flow topology and vortex stability in a curved duct

Abstract: SUMMARYWe performed incompressible flow simulation in a square duct with 90 • bend and a curvature radius of 2.3 to extend our understanding of the vortical flow development in the bend. The solutions for the flow investigated at the Reynolds number of Re = 790 are obtained in a tri-quadratic element system, where velocities stagger the pressure working variable, using the streamline-upwind finite element model and the BiCGSTAB iterative solver. The simulated results reveal that centrifugal force convects the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…Another comparison was conducted with the experimental data of Humphrey et al [26] for flow in a 90 • square bend with strong curvature (Re = 790, = 0.4348). This flow problem has been studied numerically by many researchers using a variety of methods [27][28][29][30]. Figure 10 shows normalized axial velocity profiles at two different radial locations r * = 0.3 and r * = 0.7 for angles = 60 • and 90 • where r * = (r −r o )/(r i −r o ) and r i and r o are the inner and outer diameters, respectively.…”
Section: D Steady State Flow In Curved Ductsmentioning
confidence: 99%
See 1 more Smart Citation
“…Another comparison was conducted with the experimental data of Humphrey et al [26] for flow in a 90 • square bend with strong curvature (Re = 790, = 0.4348). This flow problem has been studied numerically by many researchers using a variety of methods [27][28][29][30]. Figure 10 shows normalized axial velocity profiles at two different radial locations r * = 0.3 and r * = 0.7 for angles = 60 • and 90 • where r * = (r −r o )/(r i −r o ) and r i and r o are the inner and outer diameters, respectively.…”
Section: D Steady State Flow In Curved Ductsmentioning
confidence: 99%
“…Figure 10 shows normalized axial velocity profiles at two different radial locations r * = 0.3 and r * = 0.7 for angles = 60 • and 90 • where r * = (r −r o )/(r i −r o ) and r i and r o are the inner and outer diameters, respectively. The plots of Figure 10 include the numerical results of Tsai and Sheu [27], Drikakis et al [28] and Sotiropoulos et al [29] who used a finite elements approach, the artificial compressibility method and a pressure-linked method, respectively. The CVP method is applied with the FE formulation on a 40×40×345 grid along the bend.…”
Section: D Steady State Flow In Curved Ductsmentioning
confidence: 99%
“…It has also been shown that this streamwise velocity gradient increases with increasing bend turning angle. 29 The maximum mainstream velocity occurs at h ¼ 26 ( Figure 4) with a value of 1.34W b and at a radial position r* ¼ 0.90 on the symmetry plane. The developed velocity gradient then persists with downstream distance, with a reversal of the location of the peak velocity toward the outer wall, leading to a deceleration near the convex wall and an acceleration near the concave wall between h ¼ 30 and 90 .…”
Section: Fluid Phasementioning
confidence: 99%
“…Figure 3 shows the streamwise distribution of the pressure coefficient across the transverse (radial) direction for the entire length of the curved duct. The pressure coefficient C p is defined 2,29 by…”
Section: Fluid Phasementioning
confidence: 99%
“…Papadopoulos and Hatzikonstantinou (2005) numerically examined the incompressible and fully developed laminar flow in a curved square duct with four internal longitudinal fins using alternating direction implicit method (ADI). Tsai and Sheu (2007) studied the incompressible three dimensional laminar flow in a 90 • curved square duct with curvature ratio, i.e. the ratio of curvature radius to the edge length of duct, of 2.3 for Reynolds number of 790.…”
Section: Introductionmentioning
confidence: 99%